2011
DOI: 10.2136/vzj2011.0019
|View full text |Cite
|
Sign up to set email alerts
|

Soil Water Retention and Relative Permeability for Conditions from Oven‐Dry to Full Saturation

Abstract: Common conceptual models for unsaturated flow assume that the matric potential is attributed to the capillary force only. These models are successful at high and medium water contents but often give poor results at low water contents. The lower bound of existing water retention functions and conductivity models was extended from residual water content to the oven‐dry condition (i.e., zero water content) by defining a state‐dependent residual water content for a soil drier than a critical value. The advantages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(123 citation statements)
references
References 23 publications
2
120
0
1
Order By: Relevance
“…While this relationship, and other similar expressions, represent wet and moderately wet soil moisture conditions well, they are of limited use under dry soil conditions. Several studies have developed extensions to these functions to represent dry conditions more accurately (Webb, 2000; Khlosi et al, 2008; Zhang, 2011). The QBZ approach to modeling the flow from the irrigation system is therefore limited for two reasons: first, vapor flows are not accounted for explicitly, and second, the empirical relationship used to relate the water content to the matric potential breaks down under dry conditions.…”
Section: Methodsmentioning
confidence: 99%
“…While this relationship, and other similar expressions, represent wet and moderately wet soil moisture conditions well, they are of limited use under dry soil conditions. Several studies have developed extensions to these functions to represent dry conditions more accurately (Webb, 2000; Khlosi et al, 2008; Zhang, 2011). The QBZ approach to modeling the flow from the irrigation system is therefore limited for two reasons: first, vapor flows are not accounted for explicitly, and second, the empirical relationship used to relate the water content to the matric potential breaks down under dry conditions.…”
Section: Methodsmentioning
confidence: 99%
“…2.2.1) σ w (T K ) is the surface tension of water and w (T K ) is the static dielectric constant or relative permittivity of water; 0 = 8.85 × 10 −12 C 2 J −1 m −1 is the permittivity of free space; k B = 1.308568 × 10 −23 J K −1 is the Boltzmann constant; a = 1.6021773×10 −19 C is the electron charge; z [dimensionless] is the ion charge, for which z = 1 can be assumed; and F w [dimensionless] is a soil-specific parameter, for which Zhang (2011) found that (roughly) 10 < F w < 10 4 . The term ρ w V θ,surf in Eq.…”
Section: Functions Related To Liquid Water Transportmentioning
confidence: 99%
“…Besides the data to fit the WR of the base model and the oven‐dry pressure head, no additional data are required to fit the critical pressure value. The Rehovot sand did not respond well to the Zhang () approach, because the adsorptive component in the HC function becomes relevant at a lower absolute pressure | h | than the adsorptive component of the WR function. In similar situations, parameter h a should be fitted together with parameters ω and a to yield more reliable values.…”
Section: Resultsmentioning
confidence: 97%
“…Using the critical pressure head proposed by Zhang () as h a , its value changed to 27.55 m for the Adelanto loam and to 31.00 m for the Pachappa loam. Calculating RMSE considering all h (θ) data yielded values of 8.67·10 ‑3 and 7.44·10 ‑3 respectively.…”
Section: Resultsmentioning
confidence: 99%